1991
DOI: 10.1007/bf01296618
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacokinetics of 5-aminosalicylic acid in man following administration of intravenous bolus andper os slow-release formulation

Abstract: The fate of 5-aminosalicylic acid (5-ASA), which is used in the treatment of chronic inflammatory bowel diseases, was studied in six healthy volunteers receiving doses of 100 mg and 250 mg intravenous bolus as well as 250 mg per os (slow release). Following intravenous administration, the drug was rapidly eliminated with a plasma half-life of about 40 min, mainly due to rapid metabolism. No parent drug was recovered in feces, and the total recovery following oral administration (30%) was significantly lower th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
28
0
1

Year Published

1999
1999
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 33 publications
(30 citation statements)
references
References 17 publications
1
28
0
1
Order By: Relevance
“…Mesalazine release from this formulation has been reported to occur throughout the gastrointestinal tract [19]. It has a bioavailability of approximately 30 % [18] which is lower than that of gastroresistant tablets and may be in part be caused by a more extensive intestinal first pass metabolism which is saturable [7] (see also Table 1). Indeed, in vitro studies showed that homogenates of colonic mucosa [8] and more specifically the cytosol of human colonic epithelial cells are able to mediate mesalazine Nacetylation [20].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Mesalazine release from this formulation has been reported to occur throughout the gastrointestinal tract [19]. It has a bioavailability of approximately 30 % [18] which is lower than that of gastroresistant tablets and may be in part be caused by a more extensive intestinal first pass metabolism which is saturable [7] (see also Table 1). Indeed, in vitro studies showed that homogenates of colonic mucosa [8] and more specifically the cytosol of human colonic epithelial cells are able to mediate mesalazine Nacetylation [20].…”
Section: Discussionmentioning
confidence: 99%
“…Because of the short elimination half-life of mesalazine of clearly less than 3 hours [1,7], a prolonged release preparation is needed for maintaining plasma concentrations during a dosing interval, but also for direct delivery to any intestinal site of action. Mesalazine release from this formulation has been reported to occur throughout the gastrointestinal tract [19].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Le diverse formulazioni orali di mesalazina comportano una biodisponibilità sistemica media variabile dal 20% al 30%, con un elevato grado di variabilità interindividuale [20,21]. Qualora la mesalazina venga rilasciata precocemente nel primo tratto dell'intestino, la biodisponibilità può aumentare sensibilmente In questo lavoro, dopo aver tracciato in sintetico profilo farmacologico clinico e terapeutico della mesalazina, esamineremo anche la sua rilevanza da un punto di vista farmacoeconomico nel trattamento delle IBD.…”
Section: Farmacocinetica Clinica Forme Farmaceutiche Vie DI Somminisunclassified
“…[1][2][3][4] Mesalamine has the chemical name 5-amino-2-hydroxybenzoic acid; its structural formula is given in Figure 1. Mesalamine is thought to be the major therapeutically active part of the sulfasalazine molecule in the treatment of ulcerative colitis.…”
Section: Introductionmentioning
confidence: 99%